eXplain data conferencing for the X window system - Gratil, Glenn C. (1995)
The goal of telecommunication has always been to enable people to exchange information the way they do in face-to-face communication even though they are miles apart With a telephone, a person can speak to another who is somewhere else on the globe. With the postal system, people cu exchange letters and documents: The fix machine fets people to do both. The Internet provides alternatives to these services with programs like e-mail. tip, and talk. However, none of these technologies cater to more than two people at a time. Thus, there is a need for conferencing systems that facilitate group discussions.